Tactics of family doctors in case of syncopal states - Mykhailovska, N. S.; Grytsay, A. V.; Kachan, І. S.; Михайловська, Наталія Сергіївна; Грицай, Ганна Володимирівна; Качан, Ігор Сергійович (Запорізький державний медичний університет, 2020)
The study guide for practical classes and independent work of students of the 6th year of the international faculty of specialty "Medicine" is made in accordance with the program of the discipline "General Practice - Family Medicine". The aim of the publication is to promote a better understanding of theoretical knowledge and practical skills in the relevant topic. The study guide is also intended for interns, family doctors, physicians and other specialties who wish to supplement their knowledge of this section of medicine.
Тактика сімейного лікаря при синкопальних станах